2013
DOI: 10.1016/j.cmet.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genetic Crosstalks between mTOR and ERRα Are Key Determinants of Rapamycin-Induced Nonalcoholic Fatty Liver

Abstract: mTOR and ERRα are key regulators of common metabolic processes, including lipid homeostasis. However, it is currently unknown whether these factors cooperate in the control of metabolism. ChIP-sequencing analyses of mouse liver reveal that mTOR occupies regulatory regions of genes on a genome-wide scale including enrichment at genes shared with ERRα that are involved in the TCA cycle and lipid biosynthesis. Genetic ablation of ERRα and rapamycin treatment, alone or in combination, alter the expression of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
166
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(190 citation statements)
references
References 46 publications
16
166
3
5
Order By: Relevance
“…It has also been reported that mTORC1 (mTOR complex 1) can regulate the activity of ESRRA through ubiquitin-mediated degradation via transcriptional control of the ubiquitin-proteasome pathway (19). Furthermore, constitutive activation of mTORC1 signaling in TSC2 (tuberous sclerosis 2) null mouse embryonic fibroblasts results in an increased level of ESRRA (19).…”
mentioning
confidence: 99%
“…It has also been reported that mTORC1 (mTOR complex 1) can regulate the activity of ESRRA through ubiquitin-mediated degradation via transcriptional control of the ubiquitin-proteasome pathway (19). Furthermore, constitutive activation of mTORC1 signaling in TSC2 (tuberous sclerosis 2) null mouse embryonic fibroblasts results in an increased level of ESRRA (19).…”
mentioning
confidence: 99%
“…Previous ChIP-seq 29 and ChIP-chip 30 studies revealed that estrogen-related receptor a (ERRa, NR3B1) accumulates near genes involved in the glycolytic pathway, the TCA cycle, oxidative phosphorylation and lipid metabolism; by contrast, our ChIP-seq analysis did not show any accumulation of Ad4BP/SF-1 in genes from the latter three pathways. However, as the consensus binding sequence of ERRa is shared by Ad4BP/SF-1 (refs 4,31), we used ChIP-qPCR to examine whether Ad4BP/SF-1 accumulated on the TCA cycle genes, Suclg1 and Sdhb, where ERRa accumulates.…”
Section: Resultscontrasting
confidence: 52%
“…In mouse liver, rapamycin promotes phosphorylation of AMPKa on Thr172, which, in turn, leads to an increase in AMPK activity (Chaveroux et al 2013). A similar effect of rapamycin was observed in S. cerevisiae, in which rapamycin induced phosphorylation of Snf1 on Thr210 (Orlova et al 2006).…”
Section: Torc1 Regulation Of Ampkmentioning
confidence: 50%